Analgesic Effects of Oxycodone in Combination With Risperidone or Ziprasidone: Results From a Pilot Randomized Controlled Trial in Healthy Volunteers - Nagpal, Ameet S.; Lodge, Daniel J.; Potter, Jennifer S.; Frazer, Alan; Tragus, Robin; Curtis, Megan E.; Boley, Angela M.; Eckmann, Maxim (Frontiers in Pain Research, 2022)
Background and Objectives Patients taking opioids are at risk of developing dependence and possibly abuse. This study evaluates a novel method to reduce the abuse potential of prescription opioids by examining the analgesic efficacy of oxycodone combined with an atypical antipsychotic. Methods A randomized, double-blind, within-subjects, controlled trial in healthy volunteers was conducted at UT Health SA Pain Clinic. Fifteen volunteers with previous medical exposure to opioids were enrolled. Risperidone (2 mg) or ziprasidone (80 mg) in combination with oxycodone (5, 10, 15 mg) was administered. Pain intensity using the cold pressor test, Current Opioid Misuse Measure (COMM), Addiction Research Center Inventory (ARCI, opioid subscale), Drug likability with drug effects questionnaire (DEQ) were assessed. Results Oxycodone produced dose dependent increases in thermal analgesia on the cold pressor test that was significant at 10 and 15 mg (t=3.087, P=0.017). The combination did not significantly alter thermal analgesia. There was no significant effect of the combination on the ARCI or the POMS. Discussion and Conclusion The combination of an atypical antipsychotic with oxycodone does not alter analgesic response or increase the incidence of adverse effects when compared to oxycodone alone. Scientific Significance This intervention in chronic pain patients is unique because it utilizes FDA approved drugs in combination to reduce abuse liability. The first step, and aim of this study, is to confirm the drug combination doesn’t interfere with analgesic efficacy. Ultimately, if this combination is effective, this approach could be beneficial in management of chronic pain.